Fleshing out surfaces: Skin in French art and medicine, 1650-1850 - Fend, Mechthild (Rethinking art's histories, 2017)
Fleshing out surfaces is the first English-language book on skin and flesh tones in art. It considers flesh and skin in art theory, image making and medical discourse in seventeenth to nineteenth-century France. Describing a gradual shift between the early modern and the modern period, it argues that what artists made when imitating human nakedness was not always the same. Initially understood in terms of the body's substance, of flesh tones and body colour, it became increasingly a matter of skin, skin colour and surfaces. Each chapter is dedicated to a different notion of skin and its colour, from flesh tones via a membrane imbued with nervous energy to hermetic borderline. Looking in particular at works by Fragonard, David, Girodet, Benoist and Ingres, the focus is on portraits, as facial skin is a special arena for testing painterly skills and a site where the body and the image become equally expressive.